Antisocial behaviour among Malaysian adolescents - T'ng, Soo Ting (2011)
There was an alarming increase of violent crimes among juveniles within these few years in Malaysia that jeopardized the healthy development of the future generation. Hence, this study was aimed to examine the demographic variables (age, sex, racial, and religious groups) in antisocial behaviour among Malaysian adolescents. Survey method with stratified random sampling was implemented in this study by controlling three variables that consisted of age, sex and racial groups, but not religious groups. In this research population, participants (N= 120) were students from three secondary schools: Sekolah Menangah Jenis Kebangsaan Krian, Sekolah Menengah Kebangsaan Methodist, and Sekolah Menengah Kebangsaan Panglima Bukit Gantang. The result revealed that there was a significant difference between sex and antisocial behaviour, t(114) = 3.563, p<0.05. Male participants (M=12.652, SD=6.067) showed higher tendency in antisocial behaviour compared to female participants (M=9.255, SD=3.884). Nevertheless, there was no significant correlation of age in antisocial behaviour and no significant difference of racial groups or religious groups in antisocial behaviour. Importantly, sex differences served as the fundamental pathway for future researches to investigate in depth and to establish effective intervention programs.